2010
DOI: 10.1007/s00384-010-1056-9
|View full text |Cite
|
Sign up to set email alerts
|

The surgical stress response and postoperative immune function after laparoscopic or conventional total mesorectal excision in rectal cancer: a randomized trial

Abstract: PurposeThis study evaluated differences in stress response and immunological function following laparoscopic and conventional total mesorectal excision (TME) for rectal cancer.MethodsPatients with non-metastasized rectal cancer were prospectively randomized to open (n = 18) or laparoscopic (n = 22) TME. Blood samples were taken preoperatively (baseline), 2, 24, and 72 h following surgery. Systemic white blood cell and monocyte count, C-reactive protein, interleukin-6 (IL-6), interleukin-8 (IL-8), HLA-DR expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 17 publications
4
103
1
4
Order By: Relevance
“…This difference was found in cytokine and cell-mediated immune responses not only in animal experiments but also in clinical trials [21,22] . In our study, while leukocyte counts recovered on day 2 in the laparoscopic group, they did not recover after laparotomy.…”
Section: Clinical Datamentioning
confidence: 96%
“…This difference was found in cytokine and cell-mediated immune responses not only in animal experiments but also in clinical trials [21,22] . In our study, while leukocyte counts recovered on day 2 in the laparoscopic group, they did not recover after laparotomy.…”
Section: Clinical Datamentioning
confidence: 96%
“…3,4 Also, cellular immune responses appear to be less affected by laparoscopic colorectal resection compared with open resection as determined by total lymphocyte count, CD4 þ and CD8 þ T cells, interferon-c, and human leukocyte antigen-DR. [5][6][7][8] However, these differences are not consistent at all time intervals, and further studies are needed to fully characterize the importance of temporal changes in these markers. Furthermore, despite potential benefits, laparoscopic surgery still remains technically challenging in rectal cancer and will not be suitable for all patients.…”
mentioning
confidence: 99%
“…Previous studies also demonstrated a decrease in MHCII expression after surgery. 44, 45 Furthermore, an increase in levels of IL-6, CRP and D-lactate was reported. 4450 In all of these studies patient blood samples were collected several hours to days after closure of the abdominal cavity.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to delayed release of CRP after post-operative day 1, as demonstrated by previous studies. 45-50 The small number of patients is a limiting factor of the study, and it would be interesting to investigate more patients and/or time points after surgery.…”
Section: Discussionmentioning
confidence: 99%